Effects of Study-Integrated Well-Being Course Intervention for Different Burnout and Engagement Profiles of University Students - Kristiina Räihä; Nina Katajavuori; Kimmo Vehkalahti; Henna Asikainen (Frontline Learning Research)
As the increase in university students’ mental health problems poses significant challenges to education, new research-based ways to support students’ well-being in higher education are urgently needed. Acceptance and Commitment Therapy (ACT) has been shown to be effective in enhancing different aspects of well-being in a variety of contexts. Although study burnout has been shown to have detrimental impacts on students’ well-being and studying, not much is known about the person-oriented features of burnout risk in relation to ACT-based intervention outcomes. The aim of this study was to compare the effects of an online ACT-based course on different aspects of university students’ well-being and study ability in latent groups of students that had different levels of study burnout and engagement at the beginning of the intervention. The results of latent profile analysis (LPA) showed that students (N=352) represented four profiles at the beginning of the course: indifferent (37.8%), engaged (29%), engaged-inefficacious (13.6%), and burned-out (19.6%). The results of mixed ANOVA with repeated measures showed that psychological flexibility, well-being, study engagement and organised studying increased, and study burnout risk decreased in the whole sample of course-participating students. The changes in students’ exhaustion, well-being, psychological flexibility, and organised studying did not differ between the four burnout and engagement profiles. The profiles differed in the changes of cynicism, inadequacy and engagement. The results of this study provide new knowledge of the person-oriented features of study burnout and indicate that ACT-based course interventions can be effective in enhancing different profiles representing university students’ well-being.